How Reduced Search Costs and the Distribution of Bidder Participation Affect Auction Prices - Overby, Eric; Kannan, Karthik (Management Science, 2015)
Electronic commerce allows bidders to find and participate in auctions regardless of location. This reduction in bidders’ search costs has important effects on bidders’ participation patterns and sellers’ revenue. The “demand expansion” effect occurs when reduced search costs allow bidders to participate in more auctions. The “demand distribution” effect occurs when reduced search costs allow bidders to distribute themselves more evenly across auctions. We focus on the latter effect by modeling when a more even distribution of bidder participation across auctions increases seller revenue. We apply our analytical insights to 65,718 sequential auctions (comprising over 10 million vehicles) in the wholesale used vehicle market. We show that reduced search costs can increase seller revenue by smoothing the distribution of bidder participation across auctions, even if the aggregate amount of bidder participation remains constant. This contributes new results to the auction theory literature and generates novel insights for sellers seeking increased revenue. This paper was accepted by Lorin Hitt, information systems.